Role of AMP-activated protein kinase in the regulation of gene transcription. (April 2002) - Leclerc, I.; Viollet, B.; da Silva Xavier, G.; Kahn, A.; Rutter, G. A.
Abstract : AMP-activated protein kinase (AMPK) is a regulator of cellular metabolism in response to changes in the energy status of the cells. AMPK was known to shut down energy-consuming pathways in response to a fall in the ATP/AMP ratio by phosphorylating key enzymes of intermediate metabolism. Here we will discuss the recent evidence implicating AMPK in the regulation of gene expression in mammals, mainly in the liver and in the pancreatic β-cells.